PH-sensitive behavior of the PS-b-PDMAEMA copolymer at the air - water interface. (14th April 2021) - Bondaz, Louis; Cousin, Fabrice; Muller, François; Pantoustier, Nadège; Perrin, Patrick; Luchini, Alessandra; Goldmann, Michel; Fontaine, Philippe
Abstract: We investigated the behavior of a pH-responsive polystyrene‐ b ‐poly(2-dimethylamino)ethyl methacrylate (PS‐ b ‐PDMAEMA) diblock copolymer at the air/water interface. We synthetized different copolymers with a small hydrophobic PS block of constant length attached to polyelectrolyte PDMAEMA blocks of various lengths. We demonstrate that a Langmuir monolayer is formed with the hydrophobic collapsed PS block anchoring the hydrophilic polyelectrolyte at the interface. By combining macroscopic surface pressure measurements and specular neutron reflectivity, we studied the monolayers as a function of surface density σ and pH of the subphase. At pH = 2, the PDMAEMA is fully charged and the system at high σ behaves as a polyelectrolyte brush with chains protruding in water with a gaussian profile. At pH = 10 where the PDMAEMA is neutral, the system exhibits a phase transition between the pancake configuration to the brush configuration, with a threshold that depends on the PDMAEMA chain length, in agreement with theoretical predicted scaling laws. Graphical abstract: Image 1 Highlights: Amphiphilic Diblock Copolymers at the Air/Water interface. Polyelectrolytes. Neutron Reflectivity. Polyelectrolyte brush. Scaling laws.